La terapia intratecale nelle vasculopatie - Intrathecal therapy in vascular diseases - Rosario Russo; Marilena Cittadino; Antonio Russo (Publiediting, 2012)
Erythromelalgia is a rare clinical syndrome, characterized by erythema, burning pain and increased skin temperature in the extremities. The therapeutic treatment of this pathology is not yet standardized and both the administration of several drugs or the use of invasive techniques can be effective in some patients and without effect in others. We report the case of a 31-yearsold women affected by primary erythromelalgia that after several ineffective therapeutic treatments, was successfully treated with intrathecal ziconotide.